The recent case-law of the European Court of Human Rights on the guardianship of the administration and the separation of minors from their biological parents in cases of abandonment and/or abuse - Elósegui Itxaso, María (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The article analyzes 21 cases decided on September 12, 2023 by the ECtHR. In 12 of the applications concerning decisions of the Norwegian authorities in relation to the guardianship of minors, the judges in Strasbourg unanimously ruled that they were inadmissible because the interfe-rence with the right of parents was duly motivated by the domestic authorities and courts due to aban-donment or bad treatments. Controversial issues also included access rights, care orders and adoption. Overall, there had been no deficiencies in the decision-making process. The requests were dismissed as manifestly unfounded, considering that the facts bore no resemblance to other cases against Norway in which violations had been found. In contrast, in 9 of the applications, the Court decided that there had been a violation of Article 8 of the Convention, the right to respect for private and family life. He concluded that the facts did not differ from previous cases in which there had been a violation of the European Convention.
Keywords: Case-law of the ECTHR against Norway; Article 8 of the Convention; minors in care situation; rights of visits; misuse and/or abandonment of children